Immigrant adaptation in South Africa - Couper, Michael Patrick (Rhodes University, Faculty of Humanities, Department of Sociology, 1991)
Although the immigrant flow to South Africa has been relatively small compared to that of other immigrant receiving countries, when considered in terms of the size of South Africa's population and the fact that immigrants are restricted to the White population group, the role of immigrants in this society is considerable. Despite this, few comprehensive studies of the experiences of immigrants in South Africa have been attempted. The aim of this study is to examine the adaptation of immigrants from various countries according to a number of dimensions. Adaptation is conceived of as a dynamic and multidimensional process. A mail survey of seven immigrant groups in South Africa was undertaken during 1985. A total of 3,520 completed questionnaires were obtained from respondents representing British, German, Dutch, Italian, Portuguese, British African and Portuguese African immigrants. The relationships among dimensions of subjective adaptation (satisfaction, identification and acceptance) and objective adaptation (social, cultural, economic, religious and political adaptation) are examined. The role of settlement and citizenship intentions are also investigated, as are various factors (country of origin, length of residence, etc.) that affect immigrant adaptation in South Africa. Multivariate analyses are undertaken to explore the nature of the relationships among these variables. Following these analyses a model of immigrant adaptation in South Africa is proposed. This model is intended to serve as a framework to guide future research on the adaptation of immigrants in South Africa.
Keywords: Immigrants -- South Africa; South Africa -- Emigration and immigration -- Social aspects